2019
DOI: 10.29122/jbbi.v6i1.3237
|View full text |Cite
|
Sign up to set email alerts
|

Skrining Dan Identifikasi Mikroba Ligninolitik Pada Pengomposan Alami Tandan Kosong Kelapa Sawit

Abstract: OPEFB (oil palm empty fruit bunch) could potentially be utilized as organic fertilizer or animal feed through composting. Information on microorganisms that play important roles in the natural decomposition of OPEFB is to date not much known yet. This research was aimed to obtain and, subsequently, to molecularly identify lignin-degrading microbial isolates responsible for naturally decomposing OPEFB in the Oil Plant Plantation and Palm Oil Refinery Plant, PTPN VIII Cikasungka, Bogor. Screening for active lign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 3 publications
0
1
0
1
Order By: Relevance
“…Maka dari itu, peran kapang dan khamir sebagai mikroorganisme yang membantu memecah serat diperlukan oleh maggot. Kapang dan khamir adalah mikroorganisme yang memiliki kemampuan untuk menciptakan enzim selulase dan ligninase untuk memecah komponen selulosa dan lignin (Rupaedah et al, 2019).…”
Section: Pendahuluanunclassified
“…Maka dari itu, peran kapang dan khamir sebagai mikroorganisme yang membantu memecah serat diperlukan oleh maggot. Kapang dan khamir adalah mikroorganisme yang memiliki kemampuan untuk menciptakan enzim selulase dan ligninase untuk memecah komponen selulosa dan lignin (Rupaedah et al, 2019).…”
Section: Pendahuluanunclassified
“…(Kholis et al, 2019) stated, isolate C9 potent to degrade cellulose of biomass of eucalyptus waste. (Rupaedah et al, 2019) reported that the genus of Bacillus can degrade effectively lignin of OPEFB.…”
Section: Introductionmentioning
confidence: 99%